Painting tools & materials : a practical guide to paints, brushes, palettes and more. (Artist's toolbox., 2017)
Painting Tools & Materials provides an easy-to-use guide focusing on key concepts and practical aspects of working with specific tools, materials, and mediums for beginning artists to learn the fundamentals of painting.